ALTERNATIVE QUESTION PATTERNS IN POPULAR INDONESIAN PODCASTS - M. Rido Mantenna; Filia (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
This study examines the types of alternative questions in Indonesian podcast discourse. Alternative questions consist of two or more propositions that offer a set of choices. Out of 718 questions identified across five podcasts, a total of 34 alternative questions were found. The data were drawn from podcasts available on the YouTube channels of Grace Tahir, dr. Richard Lee, Melaney Ricardo, Deddy Corbuzier, and Denny Sumargo. The theoretical framework employed in this study is based on Quirk et al.’s theory of alternative questions and John Searle’s theory of directive speech acts. The findings reveal three main types of alternative questions: (i) explicit–explicit alternative questions, (ii) explicit–implicit alternative questions, (iii) implicit–explicit alternative questions, and one additional category (iv) contextual implicit alternative orientation. The results indicate that explicit–explicit alternative questions are the most frequently occurring type.